The Epidemiology, Clinical, and Economic Burdens of Respiratory Syncytial Virus Infections Amongst Hospitalized Children Under 5 Years of Age in Jordan: A National Multi-Center Cross-Sectional Study - Munir Abu-Helalah; Samah F. Al-Shatnawi; Mohammad Abu Lubad; Enas Al-Zayadneh; Hussein Jdaitawi; Mea’ad Harahsheh; Montaha AL-Iede; Omar Nafi; Ruba Yousef; Ihsan Almaaitah; Mai Ababneh; Toqa AlZubi; et al. (Viruses, 2024)
Respiratory syncytial virus (RSV) has been recognized as a highly important cause of morbidity and mortality among children and adults. A cross-sectional study at representative sites in Jordan was undertaken to provide an assessment of the epidemiology and health and economic burdens of RSV and influenza infections in Jordan amongst hospitalized children under 5 years old for the period between 15 November 2022 and 14 April 2023. This study involved 1000 patients with a mean age of 17.10 (SD: 16.57) months. Of these, half (n = 506, 50.6%) had positive results for RSV. Furthermore, 33% and 17.4% of the participants had positive results for RSV-B and RSV-A, respectively. The findings underscore the severity of RSV infections, where a significant proportion of the children experienced severe respiratory distress, which led to bronchiolitis and pneumonia. This study meticulously documented the clinical outcomes, including the need for intensive care, mechanical ventilation, and prolonged hospital stays. There was no statistically significant difference in the financial burdens between the RSV-positive and RSV-negative patients. This study revealed the urgent need for preventive measures to control the substantial burden of RSV among children under 5 years old in Jordan.